Penguatan Literasi Sains dan Pendidikan Karakter pada Pembelajaran IPA Abad 21 - Syahidi, Khaerus; Jufri, A. Wahab; Doyan, Aris; Kosim, Kosim; Rokhmat, Joni; Sukarso, AA (Universitas Hamzanwadi, 2023)
The purpose of this study is to describe scientific literacy and character education in 21st century science learning and to examine, describe the suitability of scientific literacy and character education for 21st century science lessons. Scientific literacy is the ability to understand science, communicate science, and apply science abilities to solving problems, in the process of learning scientific literacy is easily associated with science subjects. Scientific literacy and character education assist students in developing their potential and character values for competitiveness in the 21st century. In this study, the literature review method was used, namely by placing, obtaining, reading, and evaluating various related or related research literature. with the problem to be studied. The data described are the results of research on scientific literacy and character education in the 21st century, which have been carried out by previous researchers. The results of the literature review found that scientific literacy and character education can be integrated in 21st century science learning.